Differentially Expressed Potassium Channels Are Associated with Function of Human Effector Memory CD8+ T Cells - Sim, Ji Hyun; Kim, Kyung Soo; Park, Hyoungjun; Kim, Kyung-Jin; Lin, Haiyue; Kim, Tae-Joo; Shin, Hyun Mu; Kim, Gwanghun; Lee, Dong-Sup; Park, Chan-Wook; Lee, Dong Hun; Kang, Insoo; et al. (Frontiers in Immunology, 2017)
The voltage-gated potassium channel, Kv1.3, and the Ca2+-activated potassium channel, KCa3.1, regulate membrane potentials in T cells, thereby controlling T cell activation and cytokine production. However, little is known about the expression and function of potassium channels in human effector memory (EM) CD8+ T cells that can be further divided into functionally distinct subsets based on the expression of the interleukin (IL)-7 receptor alpha (IL-7Rα) chain. Herein, we investigated the functional expression and roles of Kv1.3 and KCa3.1 in EM CD8+ T cells that express high or low levels of the IL-7 receptor alpha chain (IL-7Rαhigh and IL-7Rαlow, respectively). In contrast to the significant activity of Kv1.3 and KCa3.1 in IL-7Rαhigh EM CD8+ T cells, IL-7Rαlow EM CD8+ T cells showed lower expression of Kv1.3 and insignificant expression of KCa3.1. Kv1.3 was involved in the modulation of cell proliferation and IL-2 production, whereas KCa3.1 affected the motility of EM CD8+ T cells. The lower motility of IL-7Rαlow EM CD8+ T cells was demonstrated using transendothelial migration and motility assays with intercellular adhesion molecule 1- and/or chemokine stromal cell-derived factor-1α-coated surfaces. Consistent with the lower migration property, IL-7Rαlow EM CD8+ T cells were found less frequently in human skin. Stimulating IL-7Rαlow EM CD8+ T cells with IL-2 or IL-15 increased their motility and recovery of KCa3.1 activity. Our findings demonstrate that Kv1.3 and KCa3.1 are differentially involved in the functions of EM CD8+ T cells. The weak expression of potassium channels in IL-7Rαlow EM CD8+ T cells can be revived by stimulation with IL-2 or IL-15, which restores the associated functions. This study suggests that IL-7Rαhigh EM CD8+ T cells with functional potassium channels may serve as a reservoir for effector CD8+ T cells during peripheral inflammation.